Correction of carriage of teenagers by the methods of physical rehabilitation - Грейда, Н. Б.; Грицай, О. С.; Кренделєва, В. У. (Slobozhanskyi Herald of Science and Sport, 2011)
In the article, facilities of forming of correct carriage of teenagers were probed 14–15 years. Done analysis of deformations of locomotorium of teenagers, mobility was probed in the lumbar department of spine. A medical physical culture, massotherapy and physiotherapy, is instrumental in forming of skills of correct maintenance of body and development of muscularly-arthral feeling. The process of correction of carriage must include such measures: exposure and removal of reasons of rachiocampsis; implementation of different physical exercises with the purpose of making healthy of organism; regular implementation of exercises; unloading of spine; training to self-control after a carriage.